Teores de fósforo, potássio e produção de alface orgânica em diferentes coberturas do solo - Mogor, Atila Francisco; Câmara, Francisco Luiz Araújo [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
The objective of this research was to evaluate the effect of the soil covering with black oats straw, and soil covered with black plastic, in phosphorous and potassium content, and biomass production of lettuce in organic system, over two years. There have been defined five handling systems for soil covering: without cover, covered with black plastic, covered with laying oats, covered with harvested oats, and covered with oats straw in natural form, for growing three cultivars of lettuce. It was used the randomized blocks design in split plot system, with four replications. It has been concluded that butter head lettuce showed biggest phosphorous content, the soils covered with oats straw promoted higher potassium accumulation and lettuce production in second year, while soil covered with black plastic promoted best lettuce production in first year.

Esse trabalho teve como objetivo avaliar o efeito da cobertura do solo com aveia preta e manutenção da palha sobre o terreno, e da cobertura do solo com plástico preto, nos teores foliares de P e K, e na produção de alface cultivada no sistema orgânico, por dois anos consecutivos. Utilizaram-se cinco tratamentos: solo sem cobertura, coberto com filme de polietileno preto, coberto com aveia deitada, coberto com aveia ceifada e solo coberto com aveia na sua forma natural, para o cultivo de três cultivares de alface, dos grupos lisa, crespa e americana. O experimento seguiu delineamento experimental de blocos ao acaso, com quatro repetições e análise estatística com parcelas subdivididas. Concluiu-se que a alface lisa acumulou mais P, em geral as palhadas promoveram maior acúmulo de K e maior produção no segundo ano, enquanto o solo coberto com plástico preto promoveu maior produção no primeiro ano.
Phosphorus and potassium content, and production of organic lettuce over different soil covering
Keywords: Lactuca sativa; Organic production; Phosphorous; Potassium; Covered soil; Avena strigosa